La comercialización de productos en el mercado Víctor Proaño de Riobamba y la satisfacción del cliente. - Maigua Guaranga, María Belén (2023)
Marketing is encompassed in actions, characteristics, strategies and processes, which are applied to introduce products and/or services efficiently in the market, so they can be offered to consumers and achieve their sale, these processes directly influence customer satisfaction, for this reason is important to know the relationship between the commercialization of products in Víctor Proaño market and customer satisfaction, for this reason an investigation was carried out based on an analysis of consumer perception that interact in the market with the purpose of analyzing the factors that influence their level of satisfaction. Through the applied instruments, these being interviews and questionnaires, they yielded results that were analyzed with descriptive statistics and SPSS V.25 software, which determined that clients have a satisfactory level, since they meet the expectations that are set. want in the product and/or service. The hypotheses raised were verified using the Chi Square test, establishing that there is a relationship between the commercialization of products from the Víctor Proaño market and customer satisfaction, concluding that the necessary factors to satisfy them are met.